THE QUALITY OF SERVICE IN DIVORCE CASES AT THE SUKABUMI RELIGIOUS COURT - Fauzi, Tia; Mulyadi, Andi; Sampurna, Rizki Hegia (DIA: Jurnal Administrasi Publik, 2024)
The purpose of this research is to determine the quality of divorce case services at the Sukabumi Religious Court, and to find out what are the driving and inhibiting factors in providing divorce case services at the Sukabumi Religious Court. The research approach used in this research is a qualitative approach. The unit of analysis in this research is the one-stop Integrated Service function. The data collection techniques used was observation, interview, and documentation. This research uses data triangulation in testing data validity or data validation. The data analysis techniques used are data reduction, data presentation, and conclusion drawing. The study highlights noteworthy improvements in the operations of the Sukabumi Religious Court, which encompass upgraded complaints desks and waiting room facilities, indicative of heightened accessibility. Demonstrating empathy awareness, measures have been taken to comprehend applicants' socio-economic conditions. Service reliability is bolstered through monthly evaluations and the provision of clear procedural information. The court's prompt resolution of complaints underscores its commendable responsiveness. Moreover, endeavours to uphold privacy and professionalism contribute to fostering confidence in the court's proceedings.